Depression, distress and self-efficacy: The impact on diabetes self-care practices - Devarajooh, C.; Chinna, K. (Public Library of Science, 2017)
The prevalence of type 2 diabetes is increasing in Malaysia, and people with diabetes have been reported to suffer from depression and diabetes distress which influences their selfefficacy in performing diabetes self-care practices. This interviewer administered, cross sectional study, conducted in the district of Hulu Selangor, Malaysia, involving 371 randomly selected patients with type 2 diabetes, recruited from 6 health clinics, aimed to examine a conceptual model regarding the association between depression, diabetes distress and self-efficacy with diabetes self-care practices using the partial least square approach of structural equation modeling. In this study, diabetes self-care practices were similar regardless of sex, age group, ethnicity, education level, diabetes complications or type of diabetes medication. This study found that self-efficacy had a direct effect on diabetes self-care practice (path coefficient = 0.438, p<0.001). Self-care was not directly affected by depression and diabetes distress, but indirectly by depression (path coefficient = -0.115, p<0.01) and diabetes distress (path coefficient = -0.122, p<0.001) via self-efficacy. In conclusion, to improve self-care practices, effort must be focused on enhancing self-efficacy levels, while not forgetting to deal with depression and diabetes distress, especially among those with poorer levels of self-efficacy.